Heterogeneity in the production of human capital - Solomon W. Polachek; Tirthatanmoy Das; Rewat Thamma-Apiroam (Institute for the Study of Labor (IZA), 2013)
We derive a tractable nonlinear earnings function which we estimate separately for each individual in the NLSY79 data. These estimates yield five important parameters for each individual: three ability measures (two representing the ability to learn and one the ability to earn), a rate of skill depreciation, and a time discount rate. In addition, we obtain a population wide estimate of the rental rate of human capital. To illustrate heterogeneity in the production of human capital, we plot the distribution of these parameters along with NLSY79 reported AFQT scores. By utilizing these parameters, we are able to verify a number of heretofore untested theorems based on the life-cycle human capital model. In addition, we are able to show how these human capital production function parameters relate to cognitive ability, personality traits, and family background. Among our results, we find: Black-white differences in ability are smaller than those exhibited in standardized tests. Blacks have higher time discount and skill depreciation rates than whites. Individuals with higher time discount rates and greater rates of skill depreciation have fewer years of school. Individuals with both a high internal locus of control and self-esteem exhibit greater ability, lower skill depreciation, and smaller time discount rates. Individuals inclined towards depression have higher time discount rates. Agreeable, open, conscientious and extrovert individuals have a greater ability to learn but not necessarily a greater ability to earn. Neurotic individuals have a lower ability to learn. Higher parental education is associated with a greater ability to learn, lower skill depreciation, and a smaller time discount rate. Educational stimuli, such as growing up in a household that subscribed to magazines, are associated with higher ability. Conversely, growing up poor is associated with lower ability.
Keywords: J24; J29; J31; J39; 330; life-cycle model; ability to learn; ability to earn; heterogeneity; earnings function